2016
DOI: 10.18632/oncotarget.10163
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new candidate therapeutic target genes in head and neck squamous cell carcinomas

Abstract: BackgroundWe aimed at identifying druggable molecular alterations at the RNA level from untreated HNSCC patients, and assessing their prognostic significance.MethodsWe retrieved 96 HNSCC patients who underwent primary surgery. Real-time quantitative RT-PCR was used to analyze a panel of 42 genes coding for major druggable proteins. Univariate and multivariate analyses were performed to assess the prognostic significance of overexpressed genes.ResultsMedian age was 56 years [35–78]. Most of patients were men (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…PD-L1 was the most studied biomarker, analyzed in 53 studies [10,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][39][40][41][42][43][44][45][46]48,50,54,[59][60][61]64,65,67,68,[70][71][72][74][75][76][77][78]80,81,86]...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-L1 was the most studied biomarker, analyzed in 53 studies [10,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][39][40][41][42][43][44][45][46]48,50,54,[59][60][61]64,65,67,68,[70][71][72][74][75][76][77][78]80,81,86]...…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, fractionated chemoradiation leads to quantifiable effects and balance between suppressive and stimulatory mechanisms, which will be helpful when combined with immune checkpoint blockade [59]. Many genes are involved in tumorigenesis pathways, but of interest, six genes (PGF, PD-L1/CD274, CDK6, EGFR, MET, VEGFA) are overexpressed in HNSCC and associated with poorer outcome [39]. Furthermore, mPDCD1 (methylated PD-1 promotor) might potentially serve as a predictive biomarker for the response to immunotherapies targeting the PD-1/PD-L1 axis [66].…”
Section: Discussionmentioning
confidence: 99%
“…There have been implications for differences in response rates between HPV-negative and HPVassociated head and neck cancers; however, these indicators have not yet led to a change in therapy guidelines (14)(15)(16)(17). Recent ground-breaking studies have identified a large variety of inter-individual and intra-individual heterogeneity as a key reason for treatment resistance (18)(19)(20)(21). Several cancer cell clones with unique sets of driver mutations can be found within a single tumor (22).…”
mentioning
confidence: 99%
“…The VEGF family serves key roles in tumor angiogenesis. It is reported that PGF is over expressed in head and neck squamous cell carcinoma, which is involved in angiogenesis (28). PGF is upregulated in breast cancer and the increased expression of PGF is associated with recurrence, metastasis and poor prognosis in patients with breast cancer (29).…”
Section: Discussionmentioning
confidence: 99%